Reducing Poverty in China: An Analysis of Social Work and Financial Management - Liu Dong, Syazwani Drani (Mathematical Statistician and Engineering Applications, 2022)
In contrast to broad reduction, focused mitigation of poverty involves the application of scientific and successful initiatives to identify and support disadvantaged populations and to manage the supportive system in line with the living conditions and backgrounds of each household. This report investigates the issues that arise when enhancing social work and financial assistance for the purpose of reducing poverty with precision in China. It makes recommendations for improving social work and financial assistance in low-income areas, as well as urging financial institutions to work more closely to government agencies to do so. In addition, social work has advanced with its idea of entitlement, its objective of aiding the underprivileged and attaining autonomy, and its premise of providing tailored services depending on the requirements. Social work is a good example of this. A social worker's job is to identify those in need, give them agency, and come up with practical solutions that will last.